ADEQUACY OF SCHOOL OPERATIONAL ASSISTANCE IN MEETING TEACHER NEEDS: KECUKUPAN BANTUAN OPERASIONAL SEKOLAH DALAM PEMENUHAN KEBUTUHAN GURU - Dewi, Sukhitta (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2019)
The role of teachers in improving the quality of education include teaching, educating, mentoring and administering. The shortage of teachers in a school will certainly have an impact on the quality of education. This study aims to analyze the adequacy of school operational assistance in meeting the needs of teachers. This study uses a mixed method, the data used are primary and secondary data. Technical data collection using interviews and documentation. From the data obtained, it shows that the monthly payment of SD honoraria in the Telomoyo Cluster Getasan District is in accordance with the implementation guidelines (technical guidelines) and technical guidelines (technical guidelines), although the reality obtained by the average monthly salary received by the PTT GTT still cannot be said to be feasible. It is hoped that this research can provide input for policy makers to always consider the adequacy of BOS Funds in each school, especially in the monthly honorary financing component. The lack of PNS teachers and the number of non-permanent teachers influences the adequacy of school operational assistance, besides the existence of teachers influences the quality of education.